Human brain organoid code of conduct - Hoppe, Meagan; Habib, Ahmed; Desai, Riya; Edwards, Lincoln; Kodavali, Chowdari; Sherry Psy, Natalie Sandel; Zinn, Pascal O. (Frontiers in Molecular Medicine, 2023)
Human brain organoids are models derived from human embryonic or induced pluripotent stem cells that mimic basic cerebral microanatomy and demonstrate simple functional neuronal networks. Brain organoids have been a rapidly expanding avenue for biomedical research in general and specifically: neural development, regeneration, and central nervous system pathophysiology. However, technology replicating functional aspects of the human brain, including electrically active neural networks, requires a responsible code of conduct. In this review, we focus the discussion on intrinsic and extrinsic ethical factors associated with organoids: intrinsic considerations arise with the growing complexity of human brain organoids, including human-animal chimerism, consciousness development, and questions of where these human-like beings fall in a moral hierarchy. Extrinsic considerations explore ethics on obtainment, manufacturing, and production of sophisticated human products. In summary, a thoughtful code of conduct using human brain organoids towards the advancement of science and medicine is crucial. This article shall facilitate a structured thought process approaching the moral landscape of organoid technology.